THE GRAMMATICAL ERRORS ON THE PARAGRAPH WRITINGS - Nadiah Ma’mun (Universitas Islam Negeri Walisongo Semarang, 2016)
This paper makes a study of grammatical error on paragraph writings of English department students. The students were asked to write the paragraph of writing as their final assignment for paragraph based writing Class. The errors found in the students’ compositions are then classified based on the surface strategy taxonomy on errors of omission, addition, misformation, and misordering. Based on the result of the research findings whole have been analyzed and the discussions which have been presented, the writer generally concluded that there are four kinds of errors which are omission, addition, misinformation and misordering. The writer found that mostly the students had grammatical error on their writing in mis-information error 43%. They consist of misinformation of adverb, V2, subject-verb agreement, article, modal, passive and word choices. It also can be concluded that most students of intermediate level made Grammatical Error in Omission and Misinformation of their paragraph writing as Dulaay at.all (1982) said that Omission of to be is common error made by students. Even tough those sentences appear without to be, article or preposition and still have meaning, student must use the Grammar correctly or accurately in writing. Most students made grammatical error in using modal, for example of error in misinformatiom “We can learning all about English, after modal must be followed by main verb. It mostly happened on students’ writing. The most common types of errors made b y students are misinformation with the number of errors is 15 or 43% and o m i s s i o n with the number of error is 11 or 31%. The type of errors with the lowest frequency is misordering errors (9%). They consist of misordering of noun phrase and misordering of adverb. These errors seem to be caused by interlingual and intralingual interference.